2015
DOI: 10.1002/uog.14668
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ulipristal acetate therapy compared with uterine artery embolization on fibroid volume and vascularity indices assessed by three-dimensional ultrasound: prospective observational study

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Using 3D power Doppler ultrasound the present study confirmed the association between vascularisation of the fibroid and fibroid growth. Methods of recording a 3D PD volume, calculating fibroid volume and vascular assessment were similar in the present study as reported in other studies . In 3D PD there are several factors influencing PD indices which should be considered.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Using 3D power Doppler ultrasound the present study confirmed the association between vascularisation of the fibroid and fibroid growth. Methods of recording a 3D PD volume, calculating fibroid volume and vascular assessment were similar in the present study as reported in other studies . In 3D PD there are several factors influencing PD indices which should be considered.…”
Section: Discussionsupporting
confidence: 75%
“…A few studies assessed fibroid volume and VIs after treatment. Czuczwar et al reported a decrease in fibroid volume and VIs after 3 months of ulipristal therapy. In the study by Chia et al 2 months of gonadotrophin‐releasing hormone analogue therapy did not change vascular indices (21 women), while fibroid volume decreased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Progesterone receptor modulators (PRMs) act directly on progesterone receptors in the smooth muscle of UFs, resulting in inhibition of cell proliferation and stimulation of apoptosis [7,8]. In women with UFs, treatment with PRMs such as mifepristone, asoprisnil and ulipristal acetate (UPA) has been shown to induce amenorrhoea [9][10][11][12][13]; furthermore, UPA has been shown to reduce UF size to a similar extent as uterine artery embolization [14]. UPA (5 mg daily) is approved in the European Union for the intermittent treatment of moderate to severe symptoms of UFs in adult women of reproductive age [15].…”
Section: Introductionmentioning
confidence: 99%
“…This effect is related, at least in part, to both the down-regulation of the angiogenic factors VEGF and ADM and their receptors, as well as to TGF-b and EGF and their receptors [14] . Additionally, a significant reduction in fibroid vascularization has been recently described by means of 3D power Doppler ultrasound after 3 months of UPA treatment [22] . Moreover, a moderate reduction in uterine artery blood flow was also reported following treatment with SPRMs [14] .…”
Section: Discussionmentioning
confidence: 99%